Arsenic sulfide nanoformulation induces erythroid differentiation in chronic myeloid leukemia cells through degradation of BCR-ABL - Wang T (Dove Medical Press, 2019)
Tao Wang,1 Tao Wen,1 Hongmin Li,2 Bing Han,2 Suisui Hao,1 Chuan Wang,1 Qiang Ma,1 Jie Meng,1 Jian Liu,1 Haiyan Xu11Department of Biomedical Engineering, Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Hematology, Peking Union Medical College Hospital, Beijing, People’s Republic of ChinaBackground: Chronic myeloid leukemia (CML) is a myeloproliferative disorder due to the existence of BCR-ABL fusion protein that allows the cells to keep proliferating uncontrollably. Although tyrosine kinase inhibitors can inhibit the activity of BCR-ABL fusion protein to trigger the cells apoptosis, drug resistance or intolerance exists in part of CML patients. Arsenic sulfide in its raw form (r-As4S4) can be orally administrated and certain therapeutic effects have been found out in the treatment of hematologic malignancies through inducing cell apoptosis.Methods: In this work, a water-dissolvable arsenic sulfide nanoformualtion (ee-As4S4) composed of As4S4 particulates with 470 nm in diameter and encapsulated by a kind of hydrophilic polymer was fabricated and applied to the CML cell line K562, K562/AO2 and primary cells from the bone marrow of CML patients.Results: Results showed that instead of inhibiting the activity of BCR-ABL, ee-As4S4 induced direct degradation of BCR-ABL in K562 cells within 6 hr incubation, followed by the occurrence of erythroid differentiation in K562 after 72 hr incubation, evidenced by the significantly upregulated CD235a and benzidine staining, which was not detectable with r-As4S4. The ee-As4S4-induced erythroid differentiation was also observed in K562/AO2 cells and bone marrow mononuclear cells of CML patients. Mechanistic studies indicated that ee-As4S4 induced autophagy by downregulating the level of intracellular ROS and hypoxia-inducible factor-1α significantly, which led to the subsequent degradation of BCR-ABL. When the concentration was increased, ee-As4S4 induced much more significant apoptosis and cell cycle arrest than r-As4S4, and the cytotoxicity of the former was about 178 times of the latter.Conclusion: ee-As4S4 was capable of inducing significant erythroid differentiation of CML cells by inducing the direct degradation of BCR-ABL; the new effect could improve hematopoietic function of CML patients as well as inhibit the leukemic cell proliferation.Keywords: chronic myeloid leukemia, erythroid differentiation, As4S4, ROS